Yield Depression in New Zealand Potato Crops Associated with Soil Compaction and Soil-Borne Diseases - Sarah M. Sinton; Richard E. Falloon; Peter D. Jamieson; Esther D. Meenken; Farhat A. Shah; Hamish E. Brown; Steven J. Dellow; Alex J. Michel; John D. Fletcher (American Journal of Potato Research, 2022)
In New Zealand, potato crop yields of 90 t ha −1 are achievable but at 55 t ha −1 , the average is becoming economically unsustainable. In 2012/13, a grower-initiated survey found that Rhizoctonia solani and Spongospora subterranea (soil-borne pathogens) and soil compaction were widespread in 11 Canterbury potato crops. Targeted areas in these crops had measured yield losses of 0 (healthy plants) – 42 (diseased, resource constrained plants) t ha −1 , limiting the farmer-measured field yield to a 56 t ha −1 average. In 2014/15, growth, water use and health of three contrasting crops were measured. Near-potential yield was achieved in one crop when disease incidence and severity were low and resources adequate. The other two crops yielded less than potential; one had an inadequate water supply and the other widespread soil-borne disease. Any suspected links between soil-borne disease, soil compaction and yield were further investigated by using them as factors in replicated experiments reported elsewhere.

Cropping History Affects Potato Yields in Canterbury, New Zealand - Sarah M. Sinton; Steven J. Dellow; Peter D. Jamieson; Richard E. Falloon; Farhat A. Shah; Esther D. Meenken; Kate K. Richards; Alex J. Michel; Craig S. Tregurtha; Jennifer M. Mcculloch (American Journal of Potato Research, 2020)

Proceedings of the 3rd International Powdery Scab Workshop - Ueli Merz; Richard E. Falloon (Potato Research, 2017)

Resistance to Spongospora subterranea induced in potato by the elicitor β-aminobutyric acid - M. Loreto Hernandez Maldonado; Richard E. Falloon; Ruth C. Butler; Anthony J. Conner; Simon R. Bulman (Australasian Plant Pathology, 2015)

Infection Risk Potential of South American Spongospora subterranea f.sp. subterranea Root Gall and Tuber Lesion Inoculum on Potato (Solanum tuberosum ssp. tuberosum) - Rebecca D. Gau; Ueli Merz; Richard E. Falloon (American Journal of Potato Research, 2015)

Professor Brian James Deverall DIC PhD FAPS FISPP FAPPS (1935–2014) - Richard E. Falloon; Greg I. Johnson; M. Lodovica Gullino (Food Security, 2014)

Agronomic factors affect powdery scab of potato and amounts of Spongospora subterranea DNA in soil - Farhat A. Shah; Richard E. Falloon; Ruth C. Butler; Ros A. Lister; Steve M. Thomas; Denis Curtin (Australasian Plant Pathology, 2014)

Low amounts of Spongospora subterranea sporosorus inoculum cause severe powdery scab, root galling and reduced water use in potato (Solanum tuberosum) - Farhat A. Shah; Richard E. Falloon; Ruth C. Butler; Ros A. Lister (Australasian Plant Pathology, 2012)

Nightshade weeds ( Solanum spp.) confirmed as hosts of the potato pathogens Meloidogyne fallax and Spongospora subterranea f. sp. subterranea - Farhat A. Shah; Richard E. Falloon; Simon R. Bulman (Australasian Plant Pathology, 2010)

Control of Powdery Scab of Potato: Towards Integrated Disease Management - Richard E. Falloon (American Journal of Potato Research, 2008)

Control of Powdery Scab of Potato: Towards Integrated Disease Management - Richard E. Falloon (American Journal of Potato Research, 2008)

Presidential Address to the 15th Biennial Australasian Plant Pathology Conference, Geelong The plant pathology contribution: collaboration for practical solutions - Richard E. Falloon (Australasian Plant Pathology, 2005)

Susceptibility of potato (Solanum tuberosum) cultivars to powdery scab (caused by Spongospora subterranea f. sp. subterranea), and relationships between tuber and root infection - Richard E. Falloon; Russell A. Genet; Andrew R. Wallace; Ruth C. Butler (Australasian Plant Pathology, 2003)